Influence of Temperature on Fluidized‐Bed Catalyst Attrition Behavior. Issue 5 (12th February 2016) - Hao, Jingai; Zhao, Yinfeng; Ye, Mao; Liu, Zhongmin
Abstract: Particle attrition is a prevalent problem in fluidized beds due to continuous moving of catalyst particles. It is always operated at high temperature either for lab‐ or industrial‐scale fluidized beds. The influence of temperature on the attrition behavior of commercial methanol‐to‐olefins (MTO) and fluid catalytic cracking (FCC) catalysts is analyzed in a three‐orifice lab‐scale fluidized bed device from room temperature to 600 °C. The two catalysts are found to be alike in attrition mode. Both change from a combination of abrasion and fragmentation to main abrasion with increasing temperature, but differ greatly in the variation of attrition index with temperature which may be attributed to the difference of material and particle properties. An empirical correlation of attrition index to attrition temperature for all test samples is proposed. Abstract : Attrition is a crucial issue in fluidized beds. The attrition of two commercial catalysts in high‐velocity air jets at high temperature is studied. The attrition modes and the influence of temperature on attrition behavior for both catalysts are discussed. In addition, an empirical correlation describing the attrition index of particles to temperature is proposed.